2009
DOI: 10.1002/lary.20058
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and gentamicin‐induced auditory hair cell loss

Abstract: Decreased hair cell loss in somatostatin-treated samples that had been exposed to gentamicin provides evidence for a protective effect of somatostatin in aminoglycoside-induced hair cell death in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…However, we have recently demonstrated that somatostatin can protect HCs from aminoglycoside toxicity in a dose-dependent manner in vitro [19]. It is reasonable to assume that this neuroprotective effect of somatostatin on HCs was mediated by SST1 or SST2 receptors; however, this has not yet been experimentally proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have recently demonstrated that somatostatin can protect HCs from aminoglycoside toxicity in a dose-dependent manner in vitro [19]. It is reasonable to assume that this neuroprotective effect of somatostatin on HCs was mediated by SST1 or SST2 receptors; however, this has not yet been experimentally proven.…”
Section: Discussionmentioning
confidence: 99%
“…In an additional study, somatostatin-producing cells were observed in the covering epithelium of the spiral prominence and in the epithelium of the intermediate and rugosal part of the endolymphatic sac [17,18]. In a recent publication from our group, we demonstrated expression of SST1 and SST2 mRNA in the postnatal rat cochlea and we reported on a dose-dependent protective effect of somatostatin on gentamicin-induced HC loss in vitro [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Both drugs damage mainly HCs, resulting in apoptotic HCs death [55,56]. Our group has demonstrated that SST can protect against aminoglycoside toxicity in a dosage-dependent manner in vitro [57]. Therefore, we hypothesized that the somatostatinergic system within the cochlea may have neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…They were maintained for 48 h in culture medium for recovery. OCs were then exposed to gentamicin at the concentration of 0.5 m M for 2, 4, 6, 9, and 15 h. We recently demonstrated that this concentration of gentamicin results in significant HC loss after 15 h [Caelers et al, 2009]. Control explants were maintained in culture medium alone for 0 and 15 h. For each time point, 1 OC was studied.…”
Section: Gentamicin Time Course Experimentsmentioning
confidence: 99%